Associations between physician home visits for the dying and place of death: A population-based retrospective cohort study. - Peter Tanuseputro; Sarah Beach; Mathieu Chalifoux; Walter P Wodchis; Amy T Hsu; Hsien Seow; Douglas G Manuel (PLoS ONE, 2018)
While most individuals wish to die at home, the reality is that most will die in hospital.To determine whether receiving a physician home visit near the end-of-life is associated with lower odds of death in a hospital.Observational retrospective cohort study, examining location of death and health care in the last year of life.Population-level study of Ontarians, a Canadian province with over 13 million residents. All decedents from April 1, 2010 to March 31, 2013 (n = 264,754).More than half of 264,754 decedents died in hospital: 45.7% died in an acute care hospital and 7.7% in complex continuing care. After adjustment for multiple factors-including patient illness, home care services, and days of being at home-receiving at least one physician home visit from a non-palliative care physician was associated with a 47% decreased odds (odds-ratio, 0.53; 95%CI: 0.51-0.55) of dying in a hospital. When a palliative care physician specialist was involved, the overall odds declined by 59% (odds ratio, 0.41; 95%CI: 0.39-0.43). The same model, adjusting for physician home visits, showed that receiving palliative home care was associated with a similar reduction (odds ratio, 0.49; 95%CI: 0.47-0.51).Location of death is strongly associated with end-of-life health care in the home. Less than one-third of the population, however, received end-of-life home care or a physician visit in their last year of life, revealing large room for improvement.